Development and validation of the dysfunctional career thoughts scale for Chinese university students - Li, Shasha; Lee, Donghyuck (Frontiers in Psychology, 2025)
Dysfunctional career thoughts significantly impede rational career decision-making and have been widely assessed using the Career Thought Inventory (CTI). However, research suggests the CTI may not fully capture Chinese university students’ cultural uniqueness, creating a measurement gap in this population. Therefore, this study aimed to develop and validate a culturally-appropriate instrument assessing dysfunctional career thoughts among Chinese university students. From 104 preliminary items evaluated for content validity, the Dysfunctional Career Thoughts Scale (DCTS) was constructed through exploratory factor analysis with 389 students. The final 20-item instrument encompasses three dimensions: (1) Self-knowledge Uncertainty and Choice Anxiety, (2) Career Decision-Making Amotivation, and (3) Career Decision-Making Process Inefficacy. Validation with 241 additional students confirmed robust construct validity through confirmatory factor analysis. Concurrent validity was established via significant negative correlations between dysfunctional career thoughts and both career decision-making self-efficacy and vocational identity. The study findings imply that Chinese university students encounter challenges related to incomplete self-awareness, external influences, and perfectionist tendencies during the career decision-making process. This culturally-sensitive instrument offers significant advantages for academic advisors and career counselors working with Chinese university populations, providing more precise identification of intervention needs. While the DCTS demonstrates considerable theoretical and practical utility, certain limitations require further investigation in future studies.